PENGARUH PELATIHAN DAN DISIPLIN TERHADAP KINERJA KARYAWAN LEVEL 5 PADA PT. QUINDOFOOD BOGOR TAHUN 2018 - Yuni Pratikno; Ary Triyanto (Aliansi : Jurnal Manajemen dan Bisnis, 2018)
This study aims to determine and analyze the effect of training and discipline on the performance of level 5 employees at PT. Quindofood Bogor. This research uses descriptive quantitative research using saturated samples of 43 level 5 employees of PT. Quindofood Bogor. Data collection in this study uses questionnaire, observation, and documentation, then with the SPSS program using the Multiple Linear Regression technique. The results of this study indicate that job training has a significant effect on the performance of level 5 employees at PT. Quindofood with t value t-table (2,085 2,021). Work discipline has a significant effect on the performance of level 5 employees at PT. Quindofood, with t value t-table (4.001 2,021). Training and discipline affect simultaneously the performance of level 5 employees at PT. Quindofood with F-count value (34,428) F-table (3.23). This shows if PT. Quindofood wants to improve the performance of level 5 employees so training and discipline must be implemented and applied consistently.